Radioiodine Labeled Anti-MIF McAb: A Potential Agent for Inflammation Imaging - Chao Zhang; Gui-hua Hou; Jian-kui Han; Jing Song; Ting Liang (Mediators of Inflammation)
Macrophage migration inhibitory factor (MIF) is a proinflammatory cytokine that may play a role in the pathogenesis of inflammation. Radiolabeled anti-MIF McAb can be used to detect in vivo inflammatory changes. The objective of this study was to investigate in vivo biology of radioiodinated anti-MIF McAb using the inflammation model mice. Anti-MIF McAb was radioiodinated with NaI125 by Iodogen method. Animal models were induced in the mice by intramuscular injection of S. aureus, E. coli, and turpentine oil. The biodistribution studies with radioiodinated anti-MIF McAb were performed on inflammation mice. The relationship between inflammatory lesions and anti-MIF McAb binding was investigated using the percent of injected dose per gram tissue (% ID/g) of tissue samples and whole-body autoradiography. The radioactivity of I125-anti-MIF McAb in the inflammatory tissue increased gradually for three inflammation models. The highest uptake was found in S. aureus group and the lowest was in E. coli group. The uptake in turpentine oil group was average. Whole-body autoradiography showed that all inflammation foci could be visualized clearly from 24 hours after injection, but 48 hours images were much clearer in accordance with the high T/NT ratio. These results demonstrate the ability of radioiodinated anti-MIF McAb to measure in vivo inflammatory events represented by high expression of MIF and suggests that radiolabeled anti-MIF McAb warrants further investigation as a potential inflammation-seeking agent for imaging to detect inflammatory disorders.